1992
DOI: 10.1177/106002809202600905
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity and Anaphylactoid Reactions to Ciprofloxacin

Abstract: As with trimethoprim/sulfamethoxazole, HIV-infected people treated with ciprofloxacin may be at special risk for hypersensitivity reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…1 A high frequency of adverse reactions has been found in HIVinfected patients treated with ciprofloxacin. [2][3][4][5] The most frequently described reactions are immediate, suggesting a type I (IgE-mediated) allergic mechanism. Clinical manifestations include pruritus, urticaria, angioedema, and shock.…”
mentioning
confidence: 98%
“…1 A high frequency of adverse reactions has been found in HIVinfected patients treated with ciprofloxacin. [2][3][4][5] The most frequently described reactions are immediate, suggesting a type I (IgE-mediated) allergic mechanism. Clinical manifestations include pruritus, urticaria, angioedema, and shock.…”
mentioning
confidence: 98%
“…There are also a number of severe anaphylactic shocks, even one with fatal outcome from ciprofloxacin, in HIV-positive patients [8]. However, to our knowledge, there is no recent study evaluating the influence of risk factors to develop a hypersensitivity to a fluoroquinolone.…”
Section: Immediate Reactionsmentioning
confidence: 96%
“…The postmarketing studies of the newer quinolones (temafloxacin, grepafloxacin, trovafloxacin) identified severe adverse effects such as anaphylactoid reactions, hemolytic anemia, QT‐interval prolongation and liver necrosis [33]. The older quinolones—ciprofloxacin, ofloxacin and levofloxacin—have not been associated with these adverse events, except for anecdotal anaphylactoid reactions due to ciprofloxacin reported in the literature [34]. Fluoroquinolones are not recommended for women during pregnancy, lactation or for young children, because of concerns about teratogenesis and cartilage toxicity.…”
Section: Antibiotic Toxicitymentioning
confidence: 99%